Listening Anxiety among English Foreign Language Students in the English Language Education Study Program at Universitas Negeri Gorontalo - Wantogia, Widya Agustina; Bay, Indri Wirahmi; Husain, Nurlaila (Madiha Press, 2025)
This study aims to identify the levels of listening anxiety experienced by fourth-semester students from the 2023 cohort of the English Language Education Study Program at the Faculty of Letters and Culture, Universitas Negeri Gorontalo. The primary focus of this research is to classify students' listening anxiety into three categories: low, moderate, and high, particularly in academic listening contexts. Listening skills are crucial in English as a Foreign Language (EFL) learning, especially at the university level, but research addressing listening anxiety at Universitas Negeri Gorontalo remains limited. This study stands out as the first to examine listening anxiety within the 2023 cohort, thus offering valuable insights to fill the existing research gap. The study applies a descriptive quantitative approach using a survey method. The research instrument used is a 33-item questionnaire adapted from the Foreign Language Listening Anxiety Scale (FLLAS) developed by Kim (2000), rated on a five-point Likert scale. The total population consisted of 131 students, with 110 students completing the questionnaire and included in the final sample. Data were collected online via Google Forms to facilitate distribution and participation. The analysis employed descriptive statistical techniques to calculate frequencies and percentages for each anxiety category. The results indicate that most students fall into the moderate to high anxiety categories. These findings offer a comprehensive understanding of listening anxiety among EFL students at Universitas Negeri Gorontalo and are expected to serve as a reference for future research while aiding lecturers in recognizing students’ affective conditions in English language learning.